Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\triangle ABC$ be a rectangular triangle with $m(\angle A)=90^{\circ}$ and $AD \perp BC, D\in[BC]$. Denote with $I_{1}$ the center of the circle inscribed in triangle $\triangle ADB$ and with $I_{2}$ center of the circle inscribed in triangle $\triangle ADC$. Prove that the circumscribed circle radius of the $\triangle AI_{1}I_{2}$ is equal with the inscribed circle radius of the the triangle $\triangle ABC$.

No idea for this problem, I make a draw, and I can't do anything more.

Thanks for your help :-)

share|cite|improve this question
up vote 2 down vote accepted

See the figure below:


Let $I_1F = r_1$, $I_2G = r_2$ and $I_1E = r_3$.

Note that $GD =r_2$, $DF = r_1$ and $I_2E = r_3$. Note also that $\triangle I_1DI_2$ is a right triangle.

So using Pytagoras' Theorem in triangles $\triangle DGI_2$, $\triangle DFI_1$, $\triangle I_1DI_2$ we get: $$DI_1= r_1 \sqrt{2},$$ $$DI_2= r_2 \sqrt{2},$$ $$I_1I_2= \sqrt{2(r_1^2+r_2^2)} \quad (1).$$

Let $m(\angle I_1AI_2)= \alpha$, as $AI_2$ is bisector of $\angle CAD$ and $AI_1$ is bisector of $\angle BAD$ we can conclude that $$\alpha = 45 ^{\circ}$$ But if $\alpha = 45 ^{\circ}$ then $\angle I_1EI_2$ is a right angle (central angle) and using Pytagoras' Theorem in $\triangle I_1EI_2$ and equation $(1)$ we get: $$r_3=\sqrt{r_1^2+r_2^2} \quad (2)$$

Now let's calculate $r$, the inscribed circle radius of $\triangle ABC$, and compare with $r_3$.

See the picture below:


We know that $\triangle ADC$, $\triangle BDA$ and $\triangle BAC$ are similar, then $$\frac{r_1}{c}=\frac{r_2}{b}=\frac{r}{a}=k \quad (3)$$ So using relation $(3)$ and Pytagoras' Theorem again ($\triangle ABC$) we get: $$a^2=b^2+c^2 \Rightarrow (\frac{r}{k})^2=(\frac{r_1}{k})^2 + (\frac{r_2}{k})^2 \Rightarrow $$ $$\Rightarrow r^2=r_1^2+r_2^2 \Rightarrow r=\sqrt{r_1^2+r_2^2} \quad (4) $$

Therefore comparing $(2)$ and $(4)$ we can conclude finally that $$r=r_3.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.